New species of Eucinetus and Noteucinetus from Australia (Coleoptera: Scirtoidea: Eucinetidae) - Lawrence, John F. (Zootaxa, 2019)
Two new species of Noteucinetus Bullians & Leschen and 12 new species of Eucinetus Germar are described from continental Australia and Tasmania. A key is given to the two genera and all described Australian species. The following new species are described: Eucinetus bicolor, sp. nov., Eucinetus bicolorellus, sp. nov., Eucinetus brindabellae, sp. nov., Eucinetus dorrigo, sp. nov., Eucinetus limitaris sp. nov., Eucinetus lorien, sp. nov., Eucinetus minutus, sp. nov., Eucinetus nebulosus, sp. nov., Eucinetus protibialis, sp. nov., Eucinetus similis, sp. nov., Eucinetus tasmaniae, sp. nov., Eucinetus tropicus, sp. nov., Noteucinetus ornatus, sp. nov., and Noteucinetus victoriae, sp. nov.